Composite vignettes of former Brazilian high-performance volleyball athletes` perspective on life skills learning and transfer - Nunes, E. L. G.; Ciampolini, V.; Santos, F.; Palheta, C. E.; Vieira do Nascimento, J.; Milisted, M. (Journal of Sports Sciences, 2021)
The purpose of this study was to examine former Brazilian high-performance volleyball athletes` perspectives on life skills learning and transfer through their experiences in sport. This qualitative study involved a narrative approach through composite vignettes. The creation of the composite vignettes included the most relevant life events and participants` perspectives through their accounts of the experience transformed in one unique voice. Participants were five former Brazilian high-performance volleyball athletes. Data were collected through rappaport timeline and semi-structured interviews. Findings showed athletes were able to learn and transfer life skills throughout their careers and later in life through an implicit approach to life skills development and transfer. The trials and tribulations of high-performance sport were, in these cases, used as life lessons that transformed into life skills used in athletes` lives beyond sport. Moving forward, more research is needed to understand the high-performance sport`s role in life skills transfer and its implication for athletes` development across socio-cultural contexts.